(3GdJbjjO hGdEjVGM deG CWdb hGZdb ef cJGH GHf GdUdGMs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s ((3eMeO Hf Ydi Hf eMeO GdTgjQ HGHf GdRQGFjJi GdZRhdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Cdge GdEjVGM eG CHge hHYO aEf CMSf eG Ufa Cgd GdMOjK ai eYQaI GdEUWdGM cJGH Ydhe dGHf GdUdGM s
(3BNQgG (B:s
(3bGd GdTGYQ Hg eeY Gddg GdbHGFd ef agQ hGdMeO ddg ChdkG hBNQG hgPG BNQ eG JjSQ LeYg Ydi cJGH Ydhe GdMOjK hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3PcQ GdfGSN Cf jhe GdfSN bO hGab jhe haGI GdeDdas
(3aQZ GdeDda ef JCdjaI SfI (B782 (3g` s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs